EVALUATION OF THE IMPLEMENTATION OF HEALTHY FOOD DELIVERY PROGRAM IN WIJAYA KUSUMAH KINDERGARTEN - Ani ABIDIN (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This aims to evaluate the context, the, the process and evaluate the product program for providing healthy food in TK Wijaya Kusumah, Ciledug, Tangerang City. This research is an evaluative type of research with a descriptive qualitative approach, in this study using the evaluation model of the Stufflebeam theory, namely CIPP (Context, Input, Process, Product). Data obtained by Interviews, observations and documents. The data used in this study are analyzed by subtracting the data, then they are presented in the form of a statement and the results are confirmed. The results of this study suggest that: The results of the evaluation of the Context of a healthy feeding program at TK Wijaya Kusumah indicate that the program has clear goals and plans. The results of evaluating the input of a healthy feeding program are known that schools and the government have a good role in running this program. The results of the evaluation of the healthy feeding program process show that the process of implementing feeding goes according to the procedures provided by the puskesmas and the problem is the lack of cooperation between parents in providing healthy food to children when the child is at home. The results of product evaluation / healthy food feeding program results in TK Wijaya Kusumah shows that the achievement of a child's health, high, and weight target is in accordance with his age and no child is experiencing severe malnutrition or stunting.